(Mis)Pricing in Loans to Businesses Owned by People of Color - William D. Bradford; Chunbei Wang; Magnus Lofstrom; Michael Verchot (Institute of Labor Economics (IZA), 2025)
This study uses survey data on small business loans granted 2022 -2023 to explore racial disparities in the terms of loans to small firms. Similar data has not been available since the 2003 Survey of Small Business Finances (SSBF). We find that for Hispanic-, Asian American- and Black-owned firms, the interest rate paid was higher than for comparable white-owned firms, adjusting for risk factors determining interest rate on loans, including the firm's industry, financial attributes, owner traits, credit history and type of loan. We also find that while Black-owned firms pay higher interest rates in states with greater broad racial disparity, while it is not statistically significant for the other minority groups. We conducted robustness tests to verify the strength of these results. If our results are nationally representative of firms that borrowed during the period we observe, then collectively on average, Asian, Black-, and Hispanic-owned businesses annually pay 9.1 billion more in interest than white-owned firms of equivalent risk attributes. Another component of credit is collateral. We find that co-signatures from third parties are required more frequently for minority firms than is justified by our economic analysis.
Keywords: D4; G2; J15; L26; M; 330; entrepreneurship; self-employment; business ownership; racial disparity; minority; loan pricing